1986
DOI: 10.1177/073168448600500105
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Studies on Advanced Fibre Hybrid Composites

Abstract: The moisture diffusion characteristics of simple (E-glass, Graphite and Kevlar) and hybrid (E-Glass-Graphite, Graphite-Kevlar and Kevlar-E-Glass) unidirectional com posites have been studied at 296 K and 343 K under water immersion conditions. The equilibrium moisture content (Mm) and diffusion coefficient (Dx) of Kevlar fibre com posites are respectively as high as 5 and 10 times those of E-glass/Graphite fibre com posites. The hybridization of impermeable fibres (E-Glass and Graphite) in a com posite does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The diffusion coefficient ( D ) is one of the important parameters of Fick’s model and shows the ability of water molecules to penetrate inside the composite structures. The values of D can be obtained from the initial slope of the plot of M t /M m against time t using the following equation 34 where…”
Section: Resultsmentioning
confidence: 99%
“…The diffusion coefficient ( D ) is one of the important parameters of Fick’s model and shows the ability of water molecules to penetrate inside the composite structures. The values of D can be obtained from the initial slope of the plot of M t /M m against time t using the following equation 34 where…”
Section: Resultsmentioning
confidence: 99%
“…Gopalan et al. [20] observed that moisture diffusion in both simple and hybrid unidirectional fiber-reinforced composites exposed to water immersion conditioning correlated well with analytical Fickian diffusion plots. However, classical Fickian diffusion model is not always adequate in predicting the moisture diffusion behavior in polymers or polymer composites in many circumstances.…”
Section: Introductionmentioning
confidence: 87%
“…It is well known that moisture and temperature degrade the performance of organic matrix composites such as graphite, Kevlar and boron reinforced epoxy [7][8][9][10][11][12][13]. Similar data for hybrid composites are very limited in literature [14][15][16][17].…”
Section: Introductionmentioning
confidence: 98%